The Heterogeneity of the Abiotic and Biotic Components of Techno-Ecosystems: View from Space and from The Earth - A.A., Protasov; Barinova, Sophia; T.N., Novoselova; Zh.F., Buseva; O.V., Tomchenko; A.A., Sylaieva; N.S., Lubskiy; V.P, Semenchenko; E.A., Sysova (European Scientific Journal, ESJ, 2019)
The article discusses the use of different methods to assess the spatial structure of the biotic and abiotic component of the techno-ecosystems of cooling ponds of thermal and nuclear power plants in Belarus and Ukraine. Field studies provide point information on the parameters of biotic and abiotic variables, whereas statistical mapping and remote sensing methods makes it possible to generalize visualization and provides a holistic picture of the spatial heterogeneity of conditions and distribution of biota. Spatial changes in cooling ponds are mainly determined by hydrodynamic conditions in the pond and the presence of anthropogenic flow of cooling water. Studies have shown that the distribution of quantitative indicators of plankton in the surface layer in the Khmelnitsky NPP cooling pond was mostly determined by the position of individualstations and sections of the pond surface relative to manmade technical and wind circulation flows. In contrary, thermal conditions had the greatest influence on the characteristics of the plankton distribution in the Lukomskoye Lake - cooling pond of Lukomlskaya TPP.